The Role of Principal Leadership Management in Enhancing Educational Quality (A Study of TK Matahari Terbit Kak Komang and TKIT Al Ibrah) - Ratna Damayanti; Taufik Harris; Suyitno Suyitno (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Improving the quality of education is a crucial aspect of early childhood education. The quality of education is significantly influenced by the principal’s leadership in managing school resources. This study aims to describe and analyze the leadership management of school principals in improving the quality of education at TK Matahari Terbit Kak Komang and TKIT Al Ibrah, the factors influencing it, and its implications for overcoming various educational challenges. This study employs a qualitative approach with a multi-site design. Data were collected through interviews, observations, and documentation involving school principals, teachers, the school committee, and parents of students. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the principal’s leadership management is implemented through the functions of planning, organizing, executing, and supervising in a systematic manner. Thus, effective leadership management by the principal contributes to the continuous improvement of educational quality and the quality of educational services.